Direct pulp capping with a self-etching adhesive system: Histopathologic evaluation in dogs' teeth - da Silva, Lea A. B.; de Freitas, Aldevina C.; de Carvalho, Fabricio K.; de Queiroz, Alexandra M.; Nelson-Filho, Paulo; Porto-Neto, Sizenando T. [UNESP] (Mosby-elsevier, 2009)
Objective. This study evaluated histopathologically the response of pulp and periradicular tissues after pulp capping with an all-in-one self-etching adhesive system in dogs' teeth.Study design. Forty teeth of 4 dogs were assigned to 3 groups according to the pulp capping material: G1 (n = 20): self-etching adhesive system; G2 (n = 10): Ca(OH)(2); G3 (n = 10): zinc oxide-eugenol. The animals were killed 7 and 70 days after pulp capping. The pieces containing the pulp-capped teeth were removed and processed for histologic analysis.Results. At 7 days, no dentin bridge formation was observed; G1 and G3 exhibited inflammatory pulpal alterations, whereas G2 presented only mild inflammatory infiltrate in the pulp tissue adjacent to the capping material, the remainder being intact. At 70 days, no specimen in G1 or G3 presented dentin bridge formation. The remaining pulp tissue exhibited severe inflammatory alterations and areas of necrosis. In G2, all specimens showed dentin bridge formation and absence of inflammation and mineralized tissue resorption. No bacteria were identified using Brown and Brenn staining techniques in all 3 groups at any observation period.Conclusion. According to the conditions of this study, direct pulp capping with the self-etching adhesive system did not allow pulp tissue repair and failed histopathologically in 100% of the cases. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2009; 108: e34-e40)